1990
DOI: 10.1007/bf01540405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intestinal permeability to [51Cr]EDTA and inflammatory activity in asymptomatic patients with Crohn's disease

Abstract: The relationship between intestinal permeability to an oral dose (100 mu Ci) of [51CR]EDTA and the inflammatory activity of Crohn's disease was studied in 63 adult patients (32 unresected and 31 resected) who underwent 162 evaluations. The results of the [51CR]EDTA test were compared with the serum levels of the acute-phase reactant proteins (APRP) and with the result of the [111In]leukocyte scanning, respectively, as an indirect and direct method to assess intestinal inflammation. In a group of healthy adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Despite other reports (2,17,26,33,39,44,45,52) that intestinal permeability is clearly increased in noninflamed IBD mucosa, especially in CD patients and their relatives, our data collectively do not indicate a primary defect in the expression of major junctional proteins in IBD. However, further as yet undefined junctional components or incompletely characterized molecules such as junction adhesion molecules (28) might be involved in the regulation of intestinal permeability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite other reports (2,17,26,33,39,44,45,52) that intestinal permeability is clearly increased in noninflamed IBD mucosa, especially in CD patients and their relatives, our data collectively do not indicate a primary defect in the expression of major junctional proteins in IBD. However, further as yet undefined junctional components or incompletely characterized molecules such as junction adhesion molecules (28) might be involved in the regulation of intestinal permeability.…”
Section: Discussioncontrasting
confidence: 99%
“…Jankowski and co-workers (19) have shown a strong correlation between the deregulation of two classic cadherin molecules, E-and P-cadherin, and the progression of human colitis (20). Furthermore, changes of intestinal permeability have been reported in patients with IBD (39,52). In UC, perturbations in permeability seem to be limited to the inflamed intestinal segment, whereas in CD, discrete intestinal permeability alterations have been observed not only in gut tissues with evident intestinal lesions but also in areas lacking any sign of macroscopic injury (10,27,38).…”
mentioning
confidence: 99%
“…Several studies have shown that the appearance of the inflammatory infiltrate in the mucosa is not the initial event [8,12]. The first histological evidence of DSS injury is a disappearance of the basal crypt with separation of the crypts from the muscularis mucosa.…”
Section: Discussionmentioning
confidence: 97%
“…Intestinal permeability may be the best current approach toward an objective, measurable, easy-to-perform, and reproducible method for assessing the degree of activity of Crohn's disease. Results from several studies indicate that the permeability rate in patients with active Crohn's disease reflects the severity and activity of the disease beyond its elevated baseline level [24][25][26]. More recently, studies have shown that shorter urinary collections can be used to achieve the same degree of accuracy of permeability assessment as with the 6-hour urine collection [27].…”
Section: Assessing Disease Activitymentioning
confidence: 96%